PERANCANGAN IKLAN LUAR RUANG DALAM MEDIA TRANSIT ADVERTISING TEXAS JUICE DI KOTA BUKITTINGGI - OKI SIKUMBANG, Dra. Zubaidah, M.Sn., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Texas Juice was founded in 2006 by Lisa Vitria derived from Maninjau. Juice Texas name stems from the idea when invited by BTV, the local television broadcast in the program